Documentary Film Procdution for Lettering Time Community to Support Brand Awareness - Reyhan Nazarindra; Sri Wulandari, S.Sn., M.A.; Aileena Solicitor.C.R.E.C, S.T,.M.Ds. (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
The Lettering Time community, established in Surabaya in 2023 under the auspices of the Better Youth Foundation, functions as a platform for young people to develop skills in lettering and calligraphy. More than just an artistic outlet, the community serves as a vital channel for communication and self-expression, offering a safe space for youth to relieve stress and express their thoughts, particularly while navigating the challenges of the quarter-life crisis. The core mission of Lettering Time is to spread goodness and inspiration through the medium of handmade letters. To achieve this mission, the community holds regular